Directionality in translation and interpreting. Preliminary report on a questionnaire survey in Croatia - Pavlović, Nataša (Array, 2008)
Directionality refers to whether translation or interpreting is done into or out of one’ s first language (L1). In traditional, prescriptive approaches, work into one’ s second language (L2) is regarded as inferior to work into L1, as evidenced by terms such as “inverse” or “reverse” translation. However, L2 translation is a regular practice in many countries around the world, particularly where “languages of limited diffusion” are used. An empirical study was designed to question prescriptive statements against L2 translation by describing the actual, real-world translation and interpreting practice. A questionnaire survey was conducted among translators and interpreters in Croatia, who were asked about their professional practice and their attitudes regarding directionality. Preliminary findings show that L2 translation is a regular practice for more than 70% of the full-time translators/interpreters in Croatia. One third of the respondents prefer L2 translation, and almost as many find this direction easier than the other. Further, 45% get better rates translating into L2. The responses also reveal that some of the traditional views concerning directionality still hold strong.